Increasing use of CTPA for the investigation of suspected pulmonary embolism. Issue 2 (17th February 2017) - Sharma, Sidharth; Lucas, Christopher D.
ABSTRACT: Objectives : Pulmonary embolism (PE) is a frequently suspected life-threatening condition that often presents with non-specific signs and symptoms. There is concern that increased availability of computerized tomography pulmonary angiogram (CTPA) is resulting in overuse in the diagnostic workup of patients presenting with cardio-respiratory symptoms. We therefore aimed to determine whether use of CTPA was increasing over time within our institution, with a consequent decrease in the diagnostic yield of PE. Furthermore, we investigated the frequency of alternative (non-PE) pathological findings revealed by CTPA. Methods : All patients who underwent CTPA in the first 15 days of eight consecutive years were enrolled retrospectively. Radiology reports and online medical records were examined. In addition, the rates of incidental PE from patients undergoing CT chest for non-suspected PE indications were also examined. Results : An increasing use of CTPA was confirmed (p = 0.04). Despite this, the diagnostic yield of PE also increased (p = 0.03). Similarly, increasing numbers of patients underwent CT chest for non-PE indications, but in this group the rate of incidental PE remained static ( 3.4%). In CPTA investigations that were negative for PE, common alternative findings were consolidation, pleural effusion and emphysema, with only 16.7% showing no abnormality. Conclusion : Although CTPA use is increasing, so is the diagnostic yield of PE. In contrast, the rate of incidental PE in those undergoing a CT chest scan for non-PE diagnosis remains relatively low and stable. This suggests that our observed increased use of CTPA is clinically appropriate.